2006
DOI: 10.1021/jf060623h
|View full text |Cite
|
Sign up to set email alerts
|

Candida rugosa Lipase LIP1-Catalyzed Transesterification To Produce Human Milk Fat Substitute

Abstract: Structured lipids (SLs) containing palmitic and oleic acids were synthesized by transesterification of tripalmitin with either oleic acid or methyl oleate as acyl donor. This SL with palmitic acid at the sn-2 position and oleic acid at sn-1,3 positions is similar in structure to human milk fat triacylglycerol. LIP1, an isoform of Candida rugosa lipase (CRL), was used as biocatalyst. The effects of reaction temperature, substrate molar ratio, and time on incorporation of oleic acid were investigated. Reaction t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
1
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(39 citation statements)
references
References 31 publications
3
33
1
1
Order By: Relevance
“…The TAG composition of the products in lipase-catalyzed reaction was reported to depend on the substrate molar ratio (Srivastava et al, 2006;Yang et al, 2003). In our study, the incorporation of caprylic and capric acid was found to increase with increasing substrate molar ratio, whereas the incorporation of palmitic acid decreased with increasing substrate molar ratio, which may be attributed to the ratio of reaction substrates.…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…The TAG composition of the products in lipase-catalyzed reaction was reported to depend on the substrate molar ratio (Srivastava et al, 2006;Yang et al, 2003). In our study, the incorporation of caprylic and capric acid was found to increase with increasing substrate molar ratio, whereas the incorporation of palmitic acid decreased with increasing substrate molar ratio, which may be attributed to the ratio of reaction substrates.…”
Section: Discussionsupporting
confidence: 48%
“…Vegetable oils (palm, soybean, hazelnut and amaranth oil), lard, butter and tripalmitin have been used as substrate to produce human milk fat substitutes. Substrate molar ratio, enzyme amount, reaction time and temperature effects on the composition of human milk fat substitutes produced have been studied (Jimenez et al, 2010;Karabulut, Turan, Vural, & Kayahan, 2007;Li et al, 2010;Nielsen, Yang, Xu, & Jacobsen, 2006;Ozcelik, Karaali, Sahin Yesilcubuk, & Kahveci, 2008;Pina-Rodriguez & Akoh, 2009;Sahin et al, 2005;Srivastava, Akoh, Chang, Lee, & Shaw, 2006;Sørensen et al, 2009;Yang et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Intensive research is being carried out to make use of the specifi cities and preferences of some lipases for synthesizing lipids with well-defi ned FA compositions and patterns of distribution, which could be used in the production of human dietary supplements and edible oils ( 26,27 ).…”
Section: Lipasesmentioning
confidence: 99%
“…To date, several methods have been used to prepare HMFSs. In particular, enzymatic acidolysis has been commonly used in several studies for HMFS preparation 5,6 .…”
Section: Introductionmentioning
confidence: 99%